Programa de formação continuada para professores de educação física : possibilidades para a construção de saberes sobre a inclusão de alunos com deficiência - Mahl, Eliane (2016)
Current international and national politics about Special Education and Inclusive Education aims to ensure that all, without exception, have equal rights to access, permanency and opportunities for satisfactory learning in all segments and areas of knowledge proposed by the Basic Education, among them, Physical Education. Based on the premise that teacher vocational training collaborates with the conjectures of the inclusive movement, this study aimed to analyze whether and how a Continuing Education Program for Physical Education teachers contributes to the construction and reconstruction of knowledge about school inclusion, enabling (more) inclusive speeches and practices, especially for students with disabilities. To meet these objectives, the research presented here was characterized as qualitative, outlined by the action research insights and data analyzed by categories. The Continuing Education Program was attended five physical education teachers and the results showed that the activities developed and built at each meeting through dialogue (search), made possible the construction and the collective reconstruction of knowledge about inclusion in the program and beyond (action); especially because the participants were able to analyze, reflect and position on what they could and should do as those who believe in inclusion, seek knowledge and enable theories and inclusive practices. Consequently, the proposed and discussed knowledge in the Continuing Education Program (search) had significant contributions to the daily action/s participants. However, this research has reinforced the responsibility of the applicability of Inclusive Education assumptions should not only be the physical education teachers or teachers of any curriculum component of basic education; since the idea of inclusion is linked to multiple government, physical, curricular and attitudinal dimensions. In this vein, this research shows that access, permanence and learning opportunities for school education of all students, will only be possible if government agencies, school administrators, teachers, families, students and community do each of you, thus enabling , a society and a truly inclusive education for all, regardless of the specifics of this "all".